Produk Diversifikasi Lengkuas Berbasis CRM dengan Strategi Up Selling dan Cross Selling - NI Wayan Priscila Yuni Praditya; Aprilia, Ina; Pebriani, Reny Aziatul (Jurnal Ilmiah Informatika Global, 2025)
The rapid development of information technology has significantly transformed consumption patterns and marketing strategies, including within the agribusiness sector in the digital era. As consumers increasingly rely on online platforms, agribusiness actors are required to adapt through technological innovation. This study focuses on the development and analysis of an online sales system for diversified galangal-based products—such as shredded galangal (serundeng) and galangal powder—as a form of digital innovation to promote local products. The research applies a Research and Development (R&D) approach using the waterfall model, which includes stages of requirement analysis, system design, implementation, testing, and evaluation. The system integrates Customer Relationship Management (CRM) concepts along with up selling and cross selling strategies to enhance customer loyalty and increase transaction value. The results indicate that the developed web-based platform successfully expands market reach, simplifies transactions, and provides valuable customer analytics to support business decision-making. The system features include a product catalog, online ordering, inventory management, social media integration, and a CRM module that facilitates customer data management and personalized promotions. The implementation of up selling and cross selling strategies proved effective in increasing the average transaction value and strengthening customer loyalty. Overall, this study demonstrates that the integration of information technology and CRM can serve as a strategic solution to enhance the competitiveness of local products made from traditional raw materials such as galangal in the modern digital marketplace.